Another window into tumor microenvironment: a case of Β‐cell rich folliculotropic mycosis fungoides responding to rituximab. (16th January 2020) - Nikolaou, Vasiliki; Iliakis, Theodoros; Marinos, Leonidas; Voudouri, Dimitra; Sidiropoulou, Polytimi; Rigopoulos, Dimitris; Stratigos, Alexander J.
Abstract: The role of tumor infiltrating immune cells in cancer development and progression is a new, promising field in oncological research. An increasing number of novel anti‐cancer agents are focussing on the tumor microenvironment. Various studies have reported on B‐cell infiltrates in mycosis fungoides (MF), but despite the substantial volume of interesting findings, solid evidence regarding their specific role in cancer is still vague. We present a case of tumor stage MF responding to rituximab. We support the hypothesis that lymphoma‐infltrating B‐cells have a significant impact on cutaneous lymphoma course and seem to be both an important and effective therapeutic target. The reduction of B‐cell population led to disease's overall remission, probably by restoring patient's immunologic tumor control.